Search for a scalar or pseudoscalar dilepton resonance produced in association with a massive vector boson or top quark-antiquark pair in multilepton events at √ =13 TeV - Tumasyan,A; Adam,W; Andrejkovic,JW; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Escalante,Del Valle A; Hussain,PS; Jeitler,M; Krammer,N; Lechner,L; et al. (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2024)
A search for beyond the standard model spin-0 bosons, , that decay into pairs of electrons, muons, or tau leptons is presented. The search targets the associated production of such bosons with a or gauge boson, or a top quark-antiquark pair, and uses events with three or four charged leptons, including hadronically decaying tau leptons. The proton-proton collision data set used in the analysis was collected at the LHC from 2016 to 2018 at a center-of-mass energy of 13 TeV, and corresponds to an integrated luminosity of 138  fb−1. The observations are consistent with the predictions from standard model processes. Upper limits are placed on the product of cross sections and branching fractions of such new particles over the mass range of 15 to 350 GeV with scalar, pseudoscalar, or Higgs-boson-like couplings, as well as on the product of coupling parameters and branching fractions. Several model-dependent exclusion limits are also presented. For a Higgs-boson-like model, limits are set on the mixing angle of the Higgs boson with the boson. For the associated production of a boson with a top quark-antiquark pair, limits are set on the coupling to top quarks. Finally, limits are set for the first time on a fermiophilic dilaton-like model with scalar couplings and a fermiophilic axion-like model with pseudoscalar couplings.